1999
DOI: 10.1016/s0022-5223(99)70321-1
|View full text |Cite
|
Sign up to set email alerts
|

A novel comparison of stentless versus stented valves in the small aortic root

Abstract: These data provide evidence that stentless and stented valves have similar hemodynamic profiles in the small aortic root when matched on true measured internal diameters. The clinical benefit of the stentless porcine valve may be due to patient selection or the lack of a rigid stent in the small aortic root, but it is not due to hemodynamic superiority over stented aortic valves of similar sizes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
31
0

Year Published

2000
2000
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(33 citation statements)
references
References 17 publications
2
31
0
Order By: Relevance
“…These data also indicate that the good hemodynamic performance of both valve types avoided a prosthesis -patient mismatch in patients with an aortic annulus diameter of at least 21 mm. The satisfactory hemodynamic performance of both valves also support conclusions from studies by Milano [6] and Rao [8], indicating that biological valves of the second and third generation may even parallel the hemodynamic performance of stentless valves when the comparison of both valve types is performed between patients with the same aortic annulus diameter.…”
Section: Discussionsupporting
confidence: 74%
“…These data also indicate that the good hemodynamic performance of both valve types avoided a prosthesis -patient mismatch in patients with an aortic annulus diameter of at least 21 mm. The satisfactory hemodynamic performance of both valves also support conclusions from studies by Milano [6] and Rao [8], indicating that biological valves of the second and third generation may even parallel the hemodynamic performance of stentless valves when the comparison of both valve types is performed between patients with the same aortic annulus diameter.…”
Section: Discussionsupporting
confidence: 74%
“…We have previously demonstrated that apparent hemodynamic differences between valves of similar labeled sizes are no longer present when the comparison is adjusted to reflect true measured dimensions. 9 Therefore, any investigation of the effect of valve size must be based on a uniform measurement that is applicable across valve manufacturers. In this study, we used the preoperative EOA indexed to body surface area (BSA) as a measure of prosthesis-patient mismatch 5 and used this ratio to evaluate long-term survival after AVR.…”
mentioning
confidence: 99%
“…In studies that evaluated the impact of concomitant surgeries on outcomes of aortic valve replacement, CABG was the most common concomitant procedure [11,18,20,21] . In our study, the most common concomitant procedures were mitral valve replacement (27.5% of patients) and myocardial revascularization (12.7% of patients).…”
Section: Discussionmentioning
confidence: 99%